Search for ZZ and ZW production in pp̄ collisions at s=1.96TeV - Acosta, D; Adelman, J; Affolder, T; Akimoto, T; Albrow, MG; Ambrose, D; Amerio, S; Amidei, D; Anastassov, A; Anikeev, K; Annovi, A; Antos, J; et al. (2005)
We present a search for ZZ and ZW vector boson pair production in pp̄ collisions at s=1.96TeV using the leptonic decay channels ZZ→llνν, ZZ→lll′l′, and ZW→lll′ν. In a data sample corresponding to an integrated luminosity of 194pb-1 collected with the Collider Detector at Fermilab, 3 candidate events are found with an expected background of 1.0±0.2 events. We set a 95% confidence level upper limit of 15.2pb on the cross section for ZZ plus ZW production, compared to the standard model prediction of 5.0±0.4pb. © 2005 The American Physical Society.